Modest decrease in severity of obesity in adolescence associates with low arterial stiffness. (October 2021) - Saner, Christoph; Laitinen, Tomi T.; Nuotio, Joel; Arnup, Sarah J.; Harcourt, Brooke E.; Bekkering, Siroon; McCallum, Zoe; Kao, Kung-Ting; Janner, Marco; Magnussen, Costan G.; Sabin, Matthew A.; Juonala, Markus; et al.
Abstract: Background and aims: Childhood obesity is associated with cardiovascular risk factors (CVRF), subclinical cardiovascular phenotypes (carotid intima-media thickness, cIMT; pulse-wave velocity, PWV; and carotid elasticity), and adult cardiovascular disease (CVD) mortality. In youth with obesity (body mass index, BMI ≥95th centile), we investigated associations between changes in adiposity and CVRF in early adolescence and subclinical cardiovascular phenotypes in late adolescence. Methods: Participants had adiposity measures (the severity of obesity in percentage >95th BMI-centile (%>95th BMI-centile)), waist circumference (WC), percentage total body fat (%BF) and CVRF (systolic blood pressure, SBP; glycoprotein acetyls, GlycA; and low-density lipoprotein cholesterol) assessed in early (mean age 10.2 ± 3.5y) and late (15.7 ± 3.7y) adolescence. Subclinical cardiovascular phenotypes were assessed in late adolescence. Multivariable regression analysis was performed. Results: Decreasing the %>95th BMI-centile was associated with carotid elasticity (0.945%/10 mmHg, p = 0.002) in females, and with PWV in males (−0.75 m/s, p < 0.001). Changes in all adiposity measures (per 1-unit increase) were associated with carotid elasticity (−0.020 to −0.063%/10 mmHg, p < 0.005), and PWV (0.011–0.045 m/s, p < 0.005). Changes in GlycA (per 50 μ mol-increase) were associated with elasticity (−0.162%/10 mmHg, p = 0.042), and changes in SBP (per 10 mmHg-increase) were associated with PWV (0.260 m/s, p < 0.001). Adjusted for change in BMI, the coefficient for GlycA was reduced by 46% and for SBP by 12%. Only male sex was associated with cIMT (+34 μ m, p = 0.006). Conclusions: In youth with obesity, decreasing or maintaining the severity of obesity, and decreasing the levels of SBP and GlycA from early to late adolescence was associated with low arterial stiffness. Graphical abstract: Image 1 Highlights: Small declines in adiposity associate with lower arterial stiffness in adolescence. Changes in glycoprotein acetyls (GlycA) associate with carotid elasticity in adolescents with obesity. Changes in blood pressure associate with pulse-wave velocity in adolescents with obesity. In adolescents with obesity, males had higher carotid intima-media thickness (cIMT) than females. Male sex was the only cardiovascular risk factor associated with arterial injury.